Patient safety attitudes of paediatric trainee physicians. Issue 6 (2nd December 2009) - Parry, G; Horowitz, L; Goldmann, D
Abstract : Objectives: To measure the patient safety attitudes of trainee physicians at an academic paediatric hospital. Design: Cross-sectional survey. Setting: An academic paediatric hospital. Participants: 209 trainee physicians based at the academic paediatric hospital in January 2004. Main outcome measures: Patient safety attitudes of trainee physicians measured using the Safety Attitudes Questionnaire (Inpatient Version) and a specific trainee survey. Results: In the Safety Attitudes Questionnaire, responses were most positive in areas associated with independent care: job satisfaction (mean factor score = 77.5) safety climate (76.1), working conditions (75.6), perception of management (70.4) and less positively in areas associated with interdependent care: teamwork climate (64.6) and stress recognition (59.1). In the trainee survey, following a principal component analysis to identify summary factors, responses were most positive in the independent areas of clinical supervision and support (75.0), communication with their immediate senior physician (65.5) and orientation of new personnel (63.9), and less positive in the interdependent areas of handoffs and multiple services, (58.1), role identification during codes (51.0) and support following an adverse event (42.8). The combined independent factor scores were higher than the interdependent (difference = 17.9, 95% CI 16.1 to 19.7, p<0.001). Fellows reported higher independent factor scores than residents (5.5, 95% CI 2.2 to 8.9, p = 0.001), but not for the interdependent scores (−0.5, 95% CI −3.6 to 2.7, p = 0.767). Conclusions: Trainees appear comfortable with caring independently for patients but less so caring interdependently. With experience, trainee physicians may experience improvement in their ability to act independently but not interdependently. Recently developed patient safety culture instruments may enable additional understanding of what could be implemented to make improvements.